Potencial alelopático de duas espécies de lacre: plantas medicinais amazônicas - Lima, Nathasha Koide (Brasil, 2024)
The genus Vismia Vand is composed of individuals identified as typical pioneer tree species. The species Vismia guianensis and Vismia cayenensis, known as seals in the Amazon, are mainly used for medicinal purposes in the region, mainly in the treatment of skin conditions. The objective of the present research was to evaluate the allelopathic potential of aqueous extracts of Vismia, on seed germination and initial development of lettuce (Lactuca sativa). The study was carried out in a completely randomized design, in a factorial scheme with an isolated control [(2 x 2 x 2) + 1], being: two species of Vismia, two types of materials (fresh leaves and twigs, separated) and two concentrations, 50 and 100%, beyond control. The results were subjected to normality and homogeneity error tests and then to analysis of variance (ANOVA) and the resulting means were compared with each other applying the Tukey test at a 5% level of significance, using the Rbio statistical software. Based on the results, it was verified that the extracts of V. guianensis and V. cayennensis did not present negative allelopathic effects on the variables related to lettuce seed germination and seedling hypocotyl length. However, the Allelopathic Effect Index indicated that both extracts caused positive and negative effects on the average seed germination speed. Lettuce radicle length was not affected by V. cayennensis extracts, but aqueous extracts of fresh V. guianensis leaves caused a negative effect on radicle length. The results demonstrate that only the species V. guianensis can present negative allelopathic activity when interacting with other plants, and that the potential may be concentrated in the plant's fresh leaves.